2022
DOI: 10.7150/ijms.71912
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived from Glioma Cells under Hypoxia Promote Angiogenesis through Up-regulated Exosomal Connexin 43

Abstract: Glioblastoma multiform (GBM) is a highly aggressive primary brain tumor. Exosomes derived from glioma cells under a hypoxic microenvironment play an important role in tumor biology including metastasis, angiogenesis and chemoresistance. However, the underlying mechanisms remain to be elucidated. In this study, we aimed to explore the role of connexin 43 on exosomal uptake and angiogenesis in glioma under hypoxia. U251 cells were exposed to 3% oxygen to achieve hypoxia, and the expression levels of HIF-1α and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 49 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…Under 3% oxygen (hypoxia), the level of connexin 43 (Cx43) in exosomes secreted in the glioblastoma cell line U251 cells was elevated. However, compared with PBS (control), exosomal Cx43 remarkably promoted tube formation in human umbilical vein endothelial cells, thereby contributing to angiogenesis in hypoxic glioblastoma TME [ 79 ].…”
Section: Glioblastoma-evs and Tmementioning
confidence: 99%
“…Under 3% oxygen (hypoxia), the level of connexin 43 (Cx43) in exosomes secreted in the glioblastoma cell line U251 cells was elevated. However, compared with PBS (control), exosomal Cx43 remarkably promoted tube formation in human umbilical vein endothelial cells, thereby contributing to angiogenesis in hypoxic glioblastoma TME [ 79 ].…”
Section: Glioblastoma-evs and Tmementioning
confidence: 99%
“…Another study shows that exosomes derived from glioma cells under hypoxia promote the proliferation, tube formation, and migration of human umbilical vein endothelial cells through upregulated exosomal Cx43 [152]. A study by Villamizar et al found that exosomes derived from mesenchymal stem cells may offer a hopeful therapy for patients afflicted with cystic fibrosis (CF).…”
Section: Exosomesmentioning
confidence: 99%
“…Seminal work in this area demonstrated that Cx43 was not only present within exosomes, but formed channels that facilitated the transfer of cargo from exosomes into the recipient cells, as well as internalization of the exosomes themselves [ 316 ]. Since this report, roles for connexins within extracellular vesicles is continuing to expand [ 317 , 318 , 319 , 320 , 321 , 322 ]. Regarding cellular bioenergetics, exosomes are capable of altering cancer cell metabolism through the delivery of metabolic pathway intermediates.…”
Section: Emerging Connectionsmentioning
confidence: 99%